2018
DOI: 10.1007/s13762-018-1892-7
|View full text |Cite
|
Sign up to set email alerts
|

The association analysis for risk evaluation of significant delay occurrence in the completion date of construction project

Abstract: It is widely known that a construction project can be described as a success if it is completed on time and without cost overrun. As the strong correlation between delay in completion date of construction projects and cost overruns exists, it is necessary to manage the risk of a delay from the very beginning: even before the start of works execution. The data concerning 139 construction contracts of the highway sections already completed, as well as their completion dates, were collected. The twelve types of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
(20 reference statements)
0
23
0
Order By: Relevance
“…Finding them contributes to predictive features of association analysis. It was utilized in multiple disciplines such as: Meteorology, e.g., for rainfall predictions [ 46 ]; Biology [ 47 , 48 , 49 ]; Medicine [ 50 ] Social sciences [ 51 ]; Sales [ 41 ]; Insurance industry [ 52 ]; Quality management [ 53 ]; Construction risk assessment [ 54 ]; Bid-rigging detection [ 55 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Finding them contributes to predictive features of association analysis. It was utilized in multiple disciplines such as: Meteorology, e.g., for rainfall predictions [ 46 ]; Biology [ 47 , 48 , 49 ]; Medicine [ 50 ] Social sciences [ 51 ]; Sales [ 41 ]; Insurance industry [ 52 ]; Quality management [ 53 ]; Construction risk assessment [ 54 ]; Bid-rigging detection [ 55 ]. …”
Section: Methodsmentioning
confidence: 99%
“…• quality management in a precast concrete elements production [64], • detection of bid-rigging in the construction industry [65], • construction project risk assessment [46], • traffic safety issues [66,67].…”
Section: Association Analysis-rules Finding Toolmentioning
confidence: 99%
“…Anysz et al [27] have found the set of unfavorable conditions usually accompanying the significant delays of construction projects with the use of association analysis. This tool is suitable for uncovering the rules in data, i.e., unusually frequent simultaneous appearance of factors or phenomena [28,29].…”
Section: Introductionmentioning
confidence: 99%